The role of the introduced rusa deer Cervus timorensis for wildlife hunting in West Papua, Indonesia - Margaretha Pangau‐Adam; Marlina Flassy; Jan‐Niklas Trei; Matthias Waltert; Mahmood Soofi (Ecological Solutions and Evidence, 2022)
Abstract The rusa deer has been introduced to Merauke region and later to Vogelkop Peninsula in Indonesian New Guinea (West Papua) in 1928. It has widely dispersed across much of the West Papuan lowlands, but little is known on population size and its role for the livelihoods of rural communities. Here, our aim was to assess the population status of rusa deer, and to investigate the extent of hunting practices on this mammal in West Papua. We conducted camera trapping and line transect surveys simultaneously to estimate rusa deer population abundance in the Kwoor basin of the Tambrauw regency, Papua Barat province, Indonesia. We also interviewed hunters (n = 134), informants (n = 9) and households (n = 91) to assess hunting patterns and socioeconomic importance of rusa deer across 15 districts of the Tambrauw regency. We estimated rusa deer density within a 48‐km2 forested area at 10.34 (5.36–19.98) and 21.04 individuals/km2 using line transect and N‐mixture modelling approach using camera trapping data, respectively. Both density estimates are considerably higher than those from its native range in Java and Bali (0.08 individual/km2). Almost 92% of hunters reported that they hunted rusa deer in their traditional forests, being the most frequent amongst the 18 hunted species, particularly for commercial (62%) and subsistence (38%) purposes. Our results suggest that traditional hunting has become a significant livelihood activity and important income source in the study area. It is therefore imperative to identify potential management strategies on wildlife hunting while also considering that the high densities of introduced rusa deer may potentially exert adverse effects on native flora and fauna. This study further suggests that traditional knowledge (locally called ‘sasi’ system) and wildlife taboos still govern wildlife hunting and utilization of forest resources in West Papua, and these need to play a role in integrated community‐based wildlife management.